Preparation of Some New Pyrazine and Triazine Derivatives and Study of their Antimicrobial and Anticancer activities - ALAbady, Assma A.; Al-Majidi, Suaad M. H. (Iraqi Journal of Science, 2024)
In this study, a new series of 1,2,4-triazine and 1,2-diazine derivatives was prepared in four and three steps, respectively. In the preparation of 1,2,4-triazine derivatives. The first step included a reaction between 2-phenyl-3-aminoquinazoline-4-(3H)-one and chloroacetyl chloride in the presence of Et3N as a base to produce (1) in 83% yield. Compound (1) was then reacted in the second step with hydrazine hydrate to yield the corresponding hydrazide (2) in 80% yield. The third step of our work included a reaction of compound (2) with different compounds: α-Naphthan isocyanate to give compound (3) (90% yield); phenyl isocyanate to afford compound (4) (80% yield); phenyl isothiocyanate to yield compound (5) (85% yield); and CS2 in basic medium to provide compound (9) in 85% yield. In the fourth step, the products (3-5) were then cyclized in alkaline medium to give substituted trizines as six-membered rings (6-8) in 78-85% yields. The reaction of compound (9) with hydrazine hydrate afforded compound (10) in 80% yield. In the preparation of 1,2-diazine derivatives, compound (2) was treated with cyclic and aromatic anhydrides to give (11-15) in yields ranging from 75 to 86%. The prepared compounds were characterized by FT-IR, 13C NMR, and 1H NMR spectroscopy and measured for a number of their physical characteristics. Also, certain tests have been performed on their anti-microbial activities on fungal strains, bacterial strains, and gram-negative and gram-positive bacteria for the identification of the most sufficient of the biologically active complexes. Finally, the anticancer activity of three prepared compounds (2, 12, and 13) was tested, and the results showed good effects of these compounds against prostate cancer PC3.